Self-Assessment in EFL Writing Class: Students' Practices - Riznanda, Winny Agustia (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Self-assessment has evolved into a tool for achieving learner-centered education's objectives, which include assisting students in becoming self-sufficient academics. Regarding this idea, self-assessment was employed in a writing class in a tertiary institution in South Sumatera, Indonesia. Therefore, this study is aimed to ascertain: (1) how the students utilize the self-assessment checklist when they are editing their writings; and (2) how the students perceive about the way in which self-assessment is implemented in their essay writing class. Thus, mixed-method research, typically the explanatory sequential design was applied. For the quantitative data, 30 tertiary-level students who wrote 120 cause/effect and argumentative essays were chosen by applying purposeful sampling technique. For the qualitative data, 9 students were selected by applying the simple random sampling technique to find out their how they perceive the implementation of self-assessment in their writing class. The quantitative analysis revealed a total of 362 revisions made by the students, namely: 42.82% (155) phrase-level revision, 21.27 % (77) surface-level revision, 19.61 % (71) content-level revision, 15.19 % (55) lexical-level revision, and 1.11% (4) structural-level revision was found. In addition, based on the qualitative data, the students believed that self-assessment in essay writing provides the following advantages, such as: facilitates learning, promotes reflection, provides immediate feedback, promotes ownership, sharpen critical thinking skills, and enhances self-regulation